AN ANALYSIS OF DIRECTIVE SPEECH ACTS USED BY NAJWA SHIHAB ON CATATAN NAJWA PODCAST “SUSAHNYA JADI PEREMPUAN” - Romadhona, Ihda Rozfania; Wafa, Hosnol; Tjahyadi, Indra; Andayani, Sri (JURNAL LITERASI, 2024)
The development of podcasts is starting to look brighter every day, with many public figures across the country competing to launch podcasts via YouTube. One of them is a podcast on Najwa Shihab's YouTube channel entitled "Catatan Najwa". This study analyzes used speech acts theory by John R Searle. Searle (1975) developed five illocutionary speech acts that differed from Austin's concepts and ideas. The five theories of Illocutionary speech acts are assertive, directive, commissive, expressive, declaration.The research design in this study is a descriptive qualitative method. The utterance of Najwa Shihab on Catatan Najwa Podcast is the data of this research. This research's data source is the utterances of Najwa Shihab on Catatan Najwa Podcast. The data collection methods used in this research are observation of the Catatan Najwa Podcast, then analysis based on library study (utterance of Najwa Shihab on Catatan Najwa Podcast), and validate the analysis by rechecking data and ensuring the data is relevant to the video. The data analysis description method in this research used informal method. The content used in this research is video of Catatan Najwa Podcast entitled “Susahnya Jadi Perempuan”. The result of 80 data includes 56 data on asking acts, 6 data on request acts, 12 data on command acts, 1 data on suggestion acts, and 3 data on prohibition acts. Based on the amount of data, the dominant data was analyzed at the request acts. The result of this study is the directive speech acts used by Najwa Shihab on Catatan Najwa Podcast found on this research. Based on the results of data analysis, there are five kinds of directive speech acts used by Najwa Shihab on the Catatan Najwa Podcast entitled “Susahnya Jadi Perempuan”. This research aims to show the existence of asking, request, command, seggestion, and prohibition directive speech acts in Najwa Shihab's utterances.